Learning objects and engagement of students in Australian and New Zealand Schools - Lowe, Kate; Lee, L.; Schibeci, R.; Cummings, R.; Phillips, R.; Lake, D. (Blackwell Publishing, 2010)
This paper reports on a completed field study that examined the usability and effectiveness of learning objects designed for Australian and New Zealand primary and secondary schools. It focuses on student engagement by observing the ways students interacted with learning objects and by listening to what they said about them. Questions that guided the field study included the following: Could the students use the learning objects easily? Did they enjoy the experience? Did they engage with the intended learning? These questions are examined with reference to students at different levels of schooling, and examples drawn from the fieldwork illustrate that, while some learning objects achieved their potential as engaging multimedia educational resources, others fell short. The paper provides a detailed examination of two learning objects to reveal what worked and what created barriers or subverted the intended learning. In particular, it explores interest, challenge and importance as elements that contributed to engagement and socially constructed learning.